Multifunctional Bioinstructive 3D Architectures to Modulate Cellular Behavior. (28th July 2019) - Vaithilingam, Jayasheelan; Sanjuan‐Alberte, Paola; Campora, Simona; Rance, Graham A.; Jiang, Long; Thorpe, Jordan; Burroughs, Laurence; Tuck, Christopher J.; Denning, Chris; Wildman, Ricky D.; Hague, Richard J. M.; Alexander, Morgan R.; et al.
Abstract: Biological structures control cell behavior via physical, chemical, electrical, and mechanical cues. Approaches that allow us to build devices that mimic these cues in a combinatorial way are lacking due to there being no suitable instructive materials and limited manufacturing procedures. This challenge is addressed by developing a new conductive composite material, allowing for the fabrication of 3D biomimetic structures in a single manufacturing method based on two‐photon polymerization. The approach induces a combinatorial biostimulative input that can be tailored to a specific application. Development of the 3D architecture is performed with a chemically actuating photocurable acrylate previously identified for cardiomyocyte attachment. The material is made conductive by impregnation with multiwalled carbon nanotubes. The bioinstructive effect of 3D nano‐ and microtopography is combined with electrical stimulation, incorporating biochemical, and electromechanical cues to stimulate cells in serum‐free media. The manufactured architecture is combined with cardiomyocytes derived from human pluripotent stem cells. It is demonstrated that by mimicking biological occurring cues, cardiomyocyte behavior can be modulated. This represents a step change in the ability to manufacture 3D multifunctional biomimetic modulatory architectures. This platform technology has implications in areas spanning regenerative medicine, tissue engineering to biosensing, and may lead to more accurate models for predicting toxicity. Abstract : Biomimetic environments are engineered in this work by producing polymeric scaffolds with improved electrical conductivity and nano‐ and microtopographies. These are then used to combine electromechanical and electrochemical cues that resemble in vivo conditions and can be tuned to fit particular applications. As an exemplar, myofibril‐like structures are manufactured for the development of human‐induced pluripotent stem cell‐derived cardiomyocytes.